Mimesis / Grzegorz Grochowski. - Grochowski, Grzegorz (1970-2022) ([Wydawnictwa Uniwersytetu Warszawskiego], 1995)
Recenzja książki: Mimesis w literaturze, kulturze i sztuce / Red. Z. Mitosek. - Warszawa, 1992.